2021
DOI: 10.1371/journal.pone.0248469
|View full text |Cite
|
Sign up to set email alerts
|

Value of simple clinical parameters to predict insulin resistance among newly diagnosed patients with type 2 diabetes in limited resource settings

Abstract: Background Insulin resistance (IR) has been considered as a therapeutic target in the management of type 2 diabetes mellitus (T2DM). Readily available, simple and low cost measures to identify individuals with IR is of utmost importance for clinicians to plan optimal management strategies. Research on the associations between surrogate markers of IR and routine clinical and lipid parameters have not been carried out in Sri Lanka, a developing country with rising burden of T2DM with inadequate resources. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…These values are low in our study cohort compared to study done by Chen et al, 17 who reported a mean fasting insulin level of 10.37 µIU/mL in their study population. Wasana et al, 11 did a similar kind of study among newly detected type 2 diabetic patients and found mean fasting plasma insulin level of 18.15±10.81 µIU/mL. This could be due to low beta-cell reserve in our ethnicity as a result of low birth weight, prematurity, and malnutrition.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…These values are low in our study cohort compared to study done by Chen et al, 17 who reported a mean fasting insulin level of 10.37 µIU/mL in their study population. Wasana et al, 11 did a similar kind of study among newly detected type 2 diabetic patients and found mean fasting plasma insulin level of 18.15±10.81 µIU/mL. This could be due to low beta-cell reserve in our ethnicity as a result of low birth weight, prematurity, and malnutrition.…”
Section: Discussionmentioning
confidence: 51%
“…18 The mean value of HOMA-IR was found to be 2.22±1.75 in the present study. Wasana et al, 11 reported mean HOMA-IR 5.51±3.85 in their study cohort. In the present study, HOMA-B% showed significant negative correlation with all plasma glucose indices, namely, FPG, 2 h PPG, and HbA1c.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Traditional medicinal plants contained various compounds that had the potential as candidates for antidiabetic drugs. Studies have shown that traditional medicinal plants had strong antidiabetic activity, both in in vitro and in vivo research settings [3]. A review of traditional medicinal plants with antidiabetic activity indicated that these plants had multiple therapeutic dynamics in combating inflammation and diabetes that could be explored for the discovery of therapeutic preparations or co-treatment agents for both diseases [4].…”
Section: Introductionmentioning
confidence: 99%